2021
DOI: 10.7759/cureus.14075
|View full text |Cite
|
Sign up to set email alerts
|

Sensorineural Hearing Loss and Systemic Autoimmune Disease: The Experience of a Systemic Immune-Mediated Diseases Unit

Abstract: Background Autoimmune inner ear disease (AIED) represents less than 1% of all cases of sensorineural hearing loss (SNHL) but its frequency may be underestimated due to lack of specific clinical and laboratory criteria. AIED can be associated with a systemic autoimmune disease (SAID) in 15%-30% of the cases. The objective of the present study was to characterize the clinical and prognostic factors of a cohort of patients with AIED. Materials and methods The authors conducted a retrospective descriptive analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Studies have indicated an association between sudden SNHL and the presence of antibodies against specific inner ear antigens, including heat shock protein 70 (HSP-70), cochlin, β-tectorin, connexin 26, β-actin, choline transporter-like protein 2, and types II and IX collagen [14,15]. Description of the immune system attack on the cochlea in autoimmune and autoinflammatory diseases: inflammation is triggered, leading to irreversible damage as activated lymphocytes migrate, while autoantibodies also contribute to hearing loss and vestibular symptoms.…”
Section: Pathophysiology Of Inner Ear Diseases In Autoimmune and Auto...mentioning
confidence: 99%
“…Studies have indicated an association between sudden SNHL and the presence of antibodies against specific inner ear antigens, including heat shock protein 70 (HSP-70), cochlin, β-tectorin, connexin 26, β-actin, choline transporter-like protein 2, and types II and IX collagen [14,15]. Description of the immune system attack on the cochlea in autoimmune and autoinflammatory diseases: inflammation is triggered, leading to irreversible damage as activated lymphocytes migrate, while autoantibodies also contribute to hearing loss and vestibular symptoms.…”
Section: Pathophysiology Of Inner Ear Diseases In Autoimmune and Auto...mentioning
confidence: 99%
“…The inner ear is fully able to mount an immune response following the invasion of outside antigens. Consequently, numerous mechanisms have been proposed to underlie cochlear damage that include antibody–antigen reactions with autoantibody enhancement (type II immune responses), complement machine activation, immune-complicated depletion (type III immune responses), direct damage mediated via cytotoxic T-cells crossing the blood–labyrinth barrier and reaching the endolymphatic sac, vasculitis, micro-thrombosis, and electrochemical reactions (type IV immune responses) ( 10 , 12 , 14 , 20 , 58 ). Antigen recognition by the innate immune cells of the inner ear (neutrophils, Mφs, and dendritic cells) stimulates the release of IL-1β, which in turn triggers a series of adaptive immune responses.…”
Section: The Role Of Inner Ear Macrophages In Aiedmentioning
confidence: 99%
“…The recruitment of immunocompetent cells and the promotion of an adaptive immune response occur in the presence of immune mediators, such as IL-1β, IL-2, and TNFα ( 13 , 20 ). Studies have suggested an association between sudden sensorineural hearing loss and the presence of vestibulocochlear antibodies against inner ear antigens, such as heat shock protein 70, cochlin, β-tectorin, and types II and IX collagen ( 12 , 20 , 59 61 ).…”
Section: The Role Of Inner Ear Macrophages In Aiedmentioning
confidence: 99%
See 1 more Smart Citation
“…rheumatoid arthritis, thyroid disease, lupus, scleroderma and Sj€ ogren's syndrome) and the presence of autoantibodies (anti-Hsp70), and it favourably responds to immunosuppressant drugs. [10][11][12] The estimated prevalence of ASNHL in the population is 0.015%; however, it is probably underdiagnosed due to the stringency of the diagnostic criteria, which include anti-Hsp70 autoantibodies, reduced number of na€ ıve T cells (CD4RA) and a favourable response to immunosuppressive therapy. 7 To date, vitiligo has not yet been explored as a probable autoimmune disorder associated with ASNHL, nor the prevalence of anti-Hsp70 is known among patients with vitiligo.…”
mentioning
confidence: 99%